Somatically evoked cough responses help to identify patients with difficult-to-treat chronic cough: a six-month observational cohort studyResearch in context - Federico Lavorini; Guja Bernacchi; Carlo Fumagalli; Marianna Noale; Stefania Maggi; Donatella Mutolo; Eliana Cinelli; Giovanni A. Fontana (EClinicalMedicine, 2023)
Summary: Background: Recently we identified in patients with chronic cough a sensory dysregulation via which the urge-to-cough (UTC) or coughing are evoked mechanically from “somatic points for cough” (SPCs) in the neck and upper trunk. We investigated the prevalence and the clinical relevance of SPCs in an unselected population of patients with chronic cough. Methods: From 2018 to 2021, symptoms of 317 consecutive patients with chronic cough (233 females) were collected on four visits (V1–V4) 2 months apart at the Cough Clinic of the University Hospital in Florence (I). Participants rated the disturbance caused by the cough (0–9 modified Borg Scale). We attempted to evoke coughing and/or UTC using mechanical actions in all participants who were subsequently categorised as responsive (somatic point for cough positive, SPC+) or unresponsive (SPC−) to these actions. An association was established between chronic cough and its commonest causes; treatments were administered accordingly. Findings: 169 patients were SPC+ and had a higher baseline cough score (p < 0.01). In most of the patients, the treatments reduced (p < 0.01) cough-associated symptoms. All patients reported a decrease (p < 0.01) in cough score at V2 (from 5.70 ± 1.4 to 3.43 ± 1.9 and from 5.01 ± 1.5 to 2.74 ± 1.7 for SPC+ and SPC− patients respectively). However, whilst in SPC− patients the cough score continued to decrease indicating virtually complete cough disappearance at V4 (0.97 ± 0.8), in SPC+ patients this variable remained close to V2 values during the entire follow-up. Interpretation: Our study suggests that the assessment of SPCs may identify patients whose cough is unresponsive and are eligible for specific treatments. Funding: This work was funded by an unrestricted grant from Merck (Italy).